Therapeutic potential of agmatine in the experimental autoimmune encephalomyelitis - Stevanović, Ivana; Ninković, Milica; Stanojević, Jelena; Mančić, Bojana; Stojanović, Ivana (Vojnosanitetski pregled, 2021)
Background/Aim. Experimental autoimmune encephalomyelitis (EAE) is a model of multiple sclerosis (MS), in which we investigated the neuroprotective effect of agmatine (AGM), known as a primary amine produced via the decarboxylation of L-arginine. Methods. Dark Agouti rats were divided into groups: control (C), Complete Freund`s Adjuvant (CFA), EAE rats decapitated on the 13th day post immunization (dpi) (EAE13) and on the 20th dpi (EAE20), EAE animals given three (EAE+AGM13) and 10 (EAE+AGM20) doses of AGM, and healthy animals administered three/10 doses of AGM (AGM). Thiobarbituric acid-reacting substances (TBARS), SH groups (SH), total glutathione (GSH), glutathione peroxidase activity (GPx), superoxide dismutase activities (tSOD, MnSOD, CuZnSOD) and nitrite/nitrate concentration (NO2+NO3) were assessed in plasma and brain structures [whole encephalitic mass (WEM) and brainstem (BS)]. Results. The obtained results showed that AGM treatment successfully attenuated severe clinical deficits in EAE. Applications of AGM in EAE rats induced normalized TBARS, SH, GSH, GPx and NO in WEM. In BS, AGM expressed less prominent effects, inducing normalized TBARS, GPx and NO, but no effect on SH and GSH. In both brain structures, tSOD activity lowered and normalized at the peak and in the remission phase of the disease, post-AGM treatment. The effect of AGM on the MnSOD in EAE was expressed in WEM/BS only in the remission phase as a reduced activity. Conclusion. Milder clinical form of developed EAE in rats indicates promising therapeutic effect of AGM in MS. The activated antioxidant system and suppressed oxidative/nitrosative stress development may denote a successful blockade of neuroinflammation initiated by EAE immunization. The study implies the capability of AGM to attenuate oxidative/nitrosative damage at the peak of EAE by modulating antioxidative defense capacity during the time-course of the disease. Thus, AGM may be considered as an agent with a beneficial effect on neuroinflammation in EAE.
Keywords: agmatine; antioxidants; encephalomyelitis; multiple sclerosis; neuroprotective agents; oxidative stress; rats; treatment